Damage accumulation in He implanted SiC at different temperatures. Issue 1 (19th November 2012) - Barbot, Jean François; Declémy, Alain; Beaufort, Marie‐France
Abstract The defect accumulation in helium‐implanted 4H–SiC was studied in a large range of temperatures through the elastic strain build‐up determined by using X‐ray diffraction measurements. The interstitial type defects formation and accumulation result in the strain build‐up that was modelled with a multi‐step damage accumulation. The gradient of strain imputed to the ion implantation processes leads to the additional step of defect accumulation where the nuclear energy loss is maximal. This phenomenon is enhanced when the formation of bubbles takes place.